2015
DOI: 10.1103/physrevc.91.055808
|View full text |Cite
|
Sign up to set email alerts
|

Role of strangeness in hybrid stars and possible observables

Abstract: We study the effects of strangeness on the quark sector of a hybrid star equation of state. Since the model we use to describe quarks is the same as the one we use to describe hadrons, we can also study the effects of strangeness on the chiral symmetry restoration and deconfinement phase transitions (first order or crossover). Finally, we analyze combined effects of hyperons and quarks on global properties of hybrid stars, like mass, radius and cooling profiles. It is found that a large amount of strangeness i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 77 publications
0
46
0
Order By: Relevance
“…As it is not clear that a first-order phase hadron-toquark transition at finite baryon density is demanded by fundamental considerations, crossover or second-order transitions have also been explored recently; see, e.g., Refs. [65,69,70]. As details of results ensuing from the model of Ref.…”
Section: Crossover Transitionsmentioning
confidence: 98%
“…As it is not clear that a first-order phase hadron-toquark transition at finite baryon density is demanded by fundamental considerations, crossover or second-order transitions have also been explored recently; see, e.g., Refs. [65,69,70]. As details of results ensuing from the model of Ref.…”
Section: Crossover Transitionsmentioning
confidence: 98%
“…In several recent papers [18][19][20][21][22][23][24], it has been shown that they may contain significant fractions of quark-hybrid matter in their centers, despite the relatively stiff nuclear equation of state (EoS) that is required to achieve such high masses. The radii of these neutron stars would be between 13 and 14 km, depending on the nuclear EoS [18,19], increasing to respectively 13.5 and 14.5 km for lighter neutron stars with canonical masses of around 1.4 M ⊙ .…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in [28], depending on the strength of the vector interaction of the strange quark, a first-order phase transition can occur. Calculating the massradius diagram of compact stars for the corresponding equation of state, this effect can be seen as a sudden cut-off of stable stellar solutions.…”
Section: Pos(icpaqgp2015)009mentioning
confidence: 67%
“…For specific choices of the relative coupling of strange quarks and non-strange quarks to the respective vector fields ξ = g sφ /g qω twin solutions of strangeness-enriched hybrid stars occur with masses around 1.7 solar masses and radii between 9 and 10 km with non-strange counterparts with large masses and larger radii. Thus, within this model there is the possibility of a class of stars with very distinct radii and a changed composition that might lead to observable effects, for instance in their cooling behaviour [28]. …”
Section: Pos(icpaqgp2015)009mentioning
confidence: 99%